Pembakuan Qira'at Ã¢â‚¬ËœAsim Riwayat hafs dalam Sejarah dan Jejaknya di Indonesia - Azammi, Mustofa (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
There are at least seven types ofÃ‚Â qiraÃ¢â‚¬â„¢atÃ‚Â (ways of QurÃ¢â‚¬â„¢anic recitation) used by Muslims to recite theÃ‚Â QurÃ¢â‚¬â„¢anÃ‚Â whose authenticity is agreed upon by Muslim scholars. However, of the seven types of QurÃ¢â‚¬â„¢anic recitation, it is that ofÃ‚Â Ã¢â‚¬ËœAsim that is used most widely by the Muslims all over the world, including in Indonesia. This article explains the factors which led to the widespread adoption and implementation of the QurÃ¢â‚¬â„¢anic recitation ofÃ‚Â Ã¢â‚¬ËœAsim, based on the narration of Hafs. Apart from the high quality of its chain of transmission and the ease of recitation, another reason for the wide dissemination of Ã¢â‚¬ËœAsimÃ¢â‚¬â„¢s recitation is the factor of (temporal) power. The spread of this version of recitation (qiraÃ¢â‚¬â„¢at) can be traced through publications of the QurÃ¢â‚¬â„¢an in various countries, includingÃ‚Â in Indonesia.